(untitled) (Current Horticulture, 2024)
The experiment was conducted to standardize container gardening techniques for fruit crops to meet the nutritional requirement of city dwellers at ICAR-CISH, Lucknow, during 2017-20. The maximum average plant biomass (1072 g/plant) was noted in guava (Psidium guajava.) and minimum (423g) in pomegranate (Punica granatum.), maximum shoot biomass (1012.11g) was recorded in plant grown in 45 cm × 45 cm and minimum (402.78g/plant) in 30 cm × 30 cm container. Destructive method was used to extract the root mass for analysis. There was maximum root biomass (506.11g) in guava and minimum (239.86g) in pomegranate, however root biomass was recorded significantly maximum (509.78g) in 45 cm ×45 cm. Root to shoot ratio was recorded maximum (0.63) in Citrus lime (Citrus aurantifolia swingle). When the plant size is similar, high root to shoot biomass is preferred. The root shoot ratio had significant correlation with stem girth and negatively correlated with fruit weight, fruit yield and root hairs diameter. Collar diameter has significantly positive correlation with plant height, fruit weight and yield. The container size as well as growing media (substrate) influenced plant growth, root and shoot biomass, fruit yield and root morphology remarkably.